Productive response of creole lambs fed integral diets with Samanea saman (Jacq.) Merr. pods (Agro Productividad, 2021)
Objective: To evaluate the productive variables and the digestibility of the nutrients of an integral diet for lambs with increasing inclusion of Samanea saman pods.Design/methodology/approach: 24 creole lambs (initial weight of 20.6 ± 0.3 kg) distributed in a completely randomized experimental design were used. The treatments were: T1, 0%, T2, 12.5%, and T3, 25% of Samanea saman pod inclusion. The productive variables and the digestibility of the nutrients were evaluated and compared with the Tukey test (? = 0.05); meanwhile, the response to the increasing content of Samanea saman was evaluated by orthogonal contrasts. The variables dry matter intake (DMI), daily weight gain (DWG) and feed conversion (FC) showed no differences (p > 0.05) between treatments.Results: Dry matter digestibility (DMD) and organic matter digestibility (OMD) increased (p